RANCANG BANGUN APLIKASI CETAK KARTU TANDA KARYAWAN PADA PT. KINTAP JAYA WATTINDO PERKEBUNAN TEBING SIRING BERBASIS WEB - Pusvita Sari, Made Shanti; Herpendi, Herpendi; Fathurrahmani, Fathurrahmani (Antivirus : Jurnal Ilmiah Teknik Informatika, 2022)
The development of information technology today allows the need for information to be fulfilled, such as the development of applications. However, currently it can solve problems for printing employee identification cards as well as managing data and presenting information including information on employee data, employee spouse data, employee child data, educational history data, work experience data, course data, emergency contact data, card design data. employee identification, job transfer data, section data and position data at PT. Kintap Jaya Wattindo Perkebunan Tebing Siring without having to use a manual system such as Microsoft Excel because it will be ineffective, inefficient and take a long time in the data collection and printing process. The above problems can be solved by utilizing the development of information technology, namely by building a web-based employee identification card printing application. This application has 100% validity where user trials are carried out with the results that all work properly as expected and are very helpful in the process of making and printing employee identification cards. With this employee card printing application, the 100% card printing process becomes faster and more efficient by presenting information about 100% of the employees more effectively and attractively.